Effect of heat stress and feeding phosphorus levels on pig electron transport chain gene expression. (9th September 2013) - Weller, M. M. D. C. A.; Alebrante, L.; Campos, P. H. R. F.; Saraiva, A.; Silva, B. A. N.; Donzele, J. L.; Oliveira, R. F. M.; Silva, F. F.; Gasparino, E.; Lopes, P. S.; Guimarães, S. E. F.
Abstract : The purpose of this study was to evaluate the effect of temperature and different levels of available phosphorus (aP) on the expression of nine genes encoding electron transport chain proteins in the Longissimus dorsi (LD) muscle of pigs. Two trials were carried out using 48 high-lean growth pigs from two different growth phases: from 15 to 30 kg (phase 1) and from 30 to 60 kg (phase 2). Pigs from growth phase 1 were fed with three different levels of dietary aP (0.107%, 0.321% or 0.535%) and submitted either to a thermoneutral (24°C and RH at 76%) or to a heat stress (34°C and RH at 70%) environment. Pigs from growth phase 2 were fed with three different levels of dietary aP (0.116%, 0.306% or 0.496%) and submitted either to a thermoneutral (22ºC and RH at 77%) or to a heat stress (32ºC and RH at 73%) environment. Heat stress decreased ( P <0.001) average daily feed intake at both growth phases. At 24°C, pigs in phase 1 fed the 0.321% aP diet had greater average daily gain and feed conversion ( P <0.05) than those fed the 0.107% or 0.535% while, at 34°C pigs fed the 0.535% aP had the best performance ( P <0.05). Pigs from phase 2 fed the 0.306% aP had best performance in both thermal environments. Gene expression profile was analyzed by quantitative real-time polymerase chain reaction. Irrespective of growing phase, the expression of six genes was lower ( P <0.05) at high temperature than at thermoneutrality. The lower expression of these genes under high temperatures evidences the effects of heat stress by decreasing oxidative metabolism, through adaptive physiological mechanisms in order to reduce heat production. In pigs from phase 1, six genes were differentially expressed across aP levels ( P <0.05) in the thermoneutral and one gene in the heat stress. In pigs from phase 2, two genes were differentially expressed across aP levels ( P <0.05) in both thermal environments. These data revealed strong evidence that phosphorus and thermal environments are key factors to regulate oxidative phosphorylation with direct implications on animal performance.